Potensi Efek Samping dan Toksisitas Senyawa Vincristine dari Tapak Dara (Catharanthus roseus L.) - Faisal Akhmal Muslikh; Fendy Prasetyawan (Universitas Ngudi Waluyo, 2024)
Tapak dara (Catharanthus roseus) is a complex and diverse plant species consisting of various varieties. Traditionally, this plant has been utilized for the treatment of malaria, constipation, diuretic, diabetes mellitus, and hypertension. The pharmacological activities are attributed to the presence of the dominant compound vincristine found in the leaves. There is limited data regarding the side effects and toxic effects of this compound, hence this research aims to provide updated information on the potential side effects and toxic effects of vincristine, which is the dominant compound in C. roseus. This research method utilizes the Way2Drug webtool (https://www.way2drug.com/passonline/predict.php), with the vincristine compound SMILES obtained from PubChem (https://pubchem.ncbi.nlm.nih.gov/). The research results indicate that vincristine has a very high potential for teratogenic activity based on the Pa value (probability